Faktor Sosio-Kultural yang Membentuk Aktivitas Pemberdayaan Perempuan di Perkebunan Teh Dataran Tinggi Jawa Barat - Wandani, Julia; Herawati, Erna; Sita , Kralawi (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This article examines the socio-cultural factors that shape women’s participation in empowerment group at a tea plantation area in Highland West Java. Applying a qualitative ethnographic method, the study draws on data obtained through participant observation and in-depth interviews with members of a women’s empowerment group, named Kalintem Sabeungkeutan. The results of this study suggest that women’s participation in empowerment activities is shaped by interrelated factors, including social capital and networks, gender relations, prevailing norms, and local cultural values. Women’s participation unfolds through everyday negotiations within household and community contexts, particularly in relation to domestic responsibilities and social expectations. Social capital, manifested in trust and a sense of togetherness, facilitates engagement in collective activities, while gendered divisions of labour and subtle social norms may constrain participation. For the women involved, empowerment is recognised through practical and relational experiences, such as gaining space to learn, feeling socially accepted, and contributing to family and community life. At the same time, differences in values, orientations toward learning, and norms of reciprocity shape who remains involved and who gradually withdraws. This study highlights the necessity of developing empowerment strategies that are culturally grounded and inclusive. Recognising empowerment as a socially embedded and relational process, this will enable women to sustain participation within their communities. The practical implications suggest the importance of expanding social capital from bonding to bridging and designing empowerment initiatives that account for women’s domestic responsibilities to enhance inclusivity and sustainability.